2016
DOI: 10.1080/09638288.2016.1231846
|View full text |Cite
|
Sign up to set email alerts
|

Screening methods for post-stroke visual impairment: a systematic review

Abstract: There is currently no standardised visual screening tool which can accurately assess all potential post-stroke visual impairments. The current tools screen for only a number of potential stroke-related impairments, which means many visual defects may be missed. The sensitivity of those which screen for all impairments is significantly lowered when patients are unable to report their visual symptoms. Future research is required to develop a tool capable of assessing stroke patients which encompasses all potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 50 publications
2
45
0
1
Order By: Relevance
“…Perimetry programmes should aim to capture this wide range of visual field loss (Keltner et al 2003;Hayreh & Zimmerman 2005;Keltner et al 2010). Stroke may affect any part of the visual pathway from the eye (in ocular stroke with altitudinal visual field defects) through to the occipital cortex with typical retrochiasmal visual field defects of homonymous hemianopia, quadrantanopia and scotomas; peripheral and/or central visual fields may be involved so quire appropriate perimetry programme choice (Rowe et al 2013;Hanna et al 2017). The use of consistent methods of visual field assessment brought about by glaucoma recommendations have streamlined clinical practice (National Institute for for Health and Clinical Excellence 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Perimetry programmes should aim to capture this wide range of visual field loss (Keltner et al 2003;Hayreh & Zimmerman 2005;Keltner et al 2010). Stroke may affect any part of the visual pathway from the eye (in ocular stroke with altitudinal visual field defects) through to the occipital cortex with typical retrochiasmal visual field defects of homonymous hemianopia, quadrantanopia and scotomas; peripheral and/or central visual fields may be involved so quire appropriate perimetry programme choice (Rowe et al 2013;Hanna et al 2017). The use of consistent methods of visual field assessment brought about by glaucoma recommendations have streamlined clinical practice (National Institute for for Health and Clinical Excellence 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop a preliminary list of outcomes for a Delphi survey we undertook an overview of seven systematic reviews of studies/trials reporting vision screening, assessment and treatment of post-stroke visual impairment 2 15–20. We extracted 119 outcomes, many of which were variations on test choices for specific visual functions.…”
Section: Methodsmentioning
confidence: 99%
“…Another possible association of diplopia may be the bidirectional horizontal nystagmus due to a posteroinferior cerebellar strokes (15). Unfortunately visual problems after stroke are under estimated in patients with stroke (16) Hanna et al (17) developed a screening tool for visual impairment post stroke.The authors concluded that the existing tools gave incomplete evaluation of visual troubles after stroke (17).Retinal ischemia can accompany diplopia and may act like a prelude for stroke as it stipulates the American Stroke Association guidelines, that is why neuroimaging is recommended immediately to identify a possible concomitant cerebral ischemia (18). There are studies (19) which demonstrates that 18.2% of patients with retinal ischemia developed a recurrent stroke after 1 month follow-up.…”
Section: Causes Of Binocular Diplopiamentioning
confidence: 99%